CALCIUM AND MAGNESIUM SILICATE AND SOIL AS ENVIRONMENTAL STABILIZERS IN THE CULTIVATION OF NILE TILAPIA LARVAE IN THE RECIRCULATION SYSTEM - Ferreira Menezes; Rodrigues Souza, Emilene; Sá Fortes Pedreira, Rodrigo; Philip Santos Amorim, Matheus; Campos Silva, Robson; Pelli, Afonso; Mattos Pedreira, Marcelo (Acta Biologica Brasiliensia, 2024)
With the intensification of production systems and the need to reduce water use, there is a greater likelihood of sudden changes in water quality, leading to fish mortality. Therefore, it is necessary to develop techniques that increase environmental homeostasis. This experiment evaluated the influence of calcium-magnesium silicate and soil compared to calcium carbonate and calcium-magnesium carbonate, traditional alkalizers, as environmental stabilizers in cultivating Nile tilapia larvae in a recirculating system. The experiment was composed of five treatments: Control) aquarium containing only water; Soil) water and soil; Calcitic) water and calcium carbonate (CaCO3); Dolomite) water and dolomitic limestone (CaCO3 MgCO3) and Silicate) water and calcium-magnesium silicate (CaSiO3 MgSiO3). After 30 days, the performance parameters, weight, standard length, total length, Fulton condition factor, weight gain, biomass, biomass gain, and survival, did not differ among treatments. Among the water quality parameters, temperature (30 °C) and oxygen (5 to 6 mg L-1) were maintained with heaters and aeration throughout the period. The parameters conductivity, pH, redox potential, salinity, turbidity, ammonia, nitrite, nitrate, alkalinity, hardness, calcium, magnesium, and silica were measured. The pH was higher in the silicate and calcitic treatments than in the control. The dolomitic treatment was higher for the redox potential than in the soil. The electrical conductivity was higher in the soil treatment than in the control. The turbidity in the soil was higher than in the other treatments. Salinity was higher in treatments that received liming products but with low values. Ammonia concentration was higher in the control treatment than in the silicate. Nitrite and nitrate concentrations did not differ between treatments. Alkalinity was higher in the silicate treatment. Hardness was higher in the calcitic, dolomitic, and silicate treatments than in control and soil. Calcium dissolved in water was higher in the calcitic and silicate treatments than in the control and soil. Silica dissolved in water was higher in silicate. Calcium-magnesium silicate is a viable and recommended alternative for liming, as it presents results equivalent to calcitic and dolomitic limestone, traditional salts for this practice, which confirms its importance in maintaining water quality and fish performance. Although the soil has a buffering capacity in the water, it is less effective than other products and deserves further study.